Priming of the Arabidopsis pattern‐triggered immunity response upon infection by necrotrophic Pectobacterium carotovorum bacteria. (4th September 2012) - Po‐Wen, Chen; Singh, Prashant; Zimmerli, Laurent
Summary: Boosted responsiveness of plant cells to stress at the onset of pathogen‐ or chemically induced resistance is called priming. The chemical β‐aminobutyric acid (BABA) enhances Arabidopsis thaliana resistance to hemibiotrophic bacteria through the priming of the salicylic acid (SA) defence response. Whether BABA increases Arabidopsis resistance to the necrotrophic bacterium Pectobacterium carotovorum ssp . carotovorum ( Pcc ) is not clear. In this work, we show that treatment with BABA protects Arabidopsis against the soft‐rot pathogen Pcc . BABA did not prime the expression of the jasmonate/ethylene‐responsive gene PLANT DEFENSIN 1.2 ( PDF1.2 ), the up‐regulation of which is usually associated with resistance to necrotrophic pathogens. Expression of the SA marker gene PATHOGENESIS RELATED 1 ( PR1 ) on Pcc infection was primed by BABA treatment, but SA‐defective mutants demonstrated a wild‐type level of BABA‐induced resistance against Pcc . BABA primed the expression of the pattern‐triggered immunity (PTI)‐responsive genes FLG22‐INDUCED RECEPTOR‐LIKE KINASE 1 ( FRK1 ), ARABIDOPSIS NON‐RACE SPECIFIC DISEASE RESISTANCE GENE (NDR1)/HAIRPIN‐INDUCED GENE (HIN1)‐LIKE 10 ( NHL10 ) and CYTOCHROME P450, FAMILY 81 ( CYP81F2 ) after inoculation with Pcc or after treatment with purified bacterial microbe‐associated molecular patterns, such as flg22 or elf26. PTI‐mediated callose deposition was also potentiated in BABA‐treated Arabidopsis, and BABA boosted Arabidopsis stomatal immunity to Pcc . BABA treatment primed the PTI response in the SA‐defective mutants SA induction deficient 2‐1 ( sid2‐1 ) and phytoalexin deficient 4‐1 ( pad4‐1 ). In addition, BABA priming was associated with open chromatin configurations in the promoter region of PTI marker genes. Our data indicate that BABA primes the PTI response upon necrotrophic bacterial infection and suggest a role for the PTI response in BABA‐induced resistance.